ANALISA PERBANDINGAN KERJASAMA PROYEK ANTARA SISTEM B.O.T DAN TURN KEY (STUDI KASUS: PROYEK MULTY INVESTMENT PT. (PERSERO) POS INDONESIA) - Martha Jaya, Nyoman (Jurnal Ilmiah Teknik Sipil; Vol. 12, No. 1 Januari 2008, 2012)
Construction project service have important role in national development growth. This important role represents challenge claiming good quality result of the construction work. Therefore, discipline of construction project management must be arranged with contract, where contract represents agreement between two people/parties or more which enforceable by law. Generally contract is conducted only for one type of work in a project. But contract can also used for development more than one type of work in one project that called Multi Investment Project. This study analyzed the characteristic of B.O.T (Build Operate Transfer) and Turn Key contract which later; then will be conducted by comparison of contact administration and financial aspect. From contract administration aspect, comparison of contract of B.O.T and Turn Key relate to FIDIC standard contract. Meanwhile, from aspect of financial, it is analyzed the cash flow during economic term of project/investment that is about 20 (twenty) years. To obtain the eligibility and advantage of investment, it was used criterion assessment of investment, that are NPV (Net Present Value) method, BCR (Benefit Cost Ratio) method, and IRR (Internal Rate Return) method. Financial Analysis of contract of B.O.T at interest rate level of 8% it is obtained NPV= + Rp.12.836.521.112,73 and BCR= 1,210973; at interest rate of 10% it is obtained NPV= + Rp.9.663.942.582,50 and BCR= 1,161926; at interest rate of 12% it is obtained NPV= + Rp.6.750.628.967,75 and BCR= 1,115084. Value of IRR was equal to 17,67840 % which is bigger than the value at interest rate of 8%, 10%, and 12% per year, which mean the project is feasible to be executed. By Turn Key (rent) contract, at interest rate level of 8% it is obtained NPV= + Rp.120.097.400.848,82 and BCR= 2,46743; at interest rate of 10% it is obtained NPV= + Rp.77.282.215.410,74 and BCR= 1,9547; at interest rate of 12% it is obtained NPV = + Rp.47.321.587.896,52 and BCR= 1,590572. Value of IRR obtained is equal to 18,31581 % which is bigger than the value at interest rate level of 8%, 10%, and 12% per year, which mean the project is feasible to be executed. By Turn Key (sell) contract, at interest rate level of 8% it is obtained NPV= + Rp.58.941.119.568,47 and BCR= 1,721056; at interest rate of 10% it is obtained NPV= + Rp.52.579.999.728,98 and BCR= 1,650291; at interest rate of 12% it is obtained NPV= + Rp.46.795.288.855,17 and BCR= 1,58464. Value of IRR obtained is equal to 37,14001% which is bigger than the value at interest rate level of 8%, 10%, and 12% per year, which mean the project is feasible to be executed.
Keywords: kontrak, B.O.T, Turn Key